OPTIMALISASI PENCITRAAN STRUKTUR BAWAH PERMUKAAN MENGGUNAKAN METODE KIRCHHOFF PRE-STACK TIME MIGRATION PADA DATA SEISMIK LAUT WETAR - Syamsurijal Rasimeng; Amelia Isti Ekarena; Bagus Sapto Mulyanto; Subarsyah Subarsyah; Andrian Wilyan Djaja (JGE (Jurnal Geofisika Eksplorasi), 2020)
Migration is one of the stages in seismic data processing aimed at returning the diffraction effect to the actual reflector point. The processing of a seismic data is adjusted to the existing problems in the data itself, so the accuracy in using the migration technique and determination of data processing parameters greatly affects the resulting seismic cross-section. Kirchhoff Pre-Stack Time Migration is one of the most used migration methods in seismic data processing because it shows better results than conventional stacking methods. The parameters that need to be noticed in the Kirchhoff migration are the migration aperture values. Based on this, variations of migration aperture values used are 75 m, 200 m and 512.5 m. The 512.5-m aperture migration value shows the best seismic cross-section results. This is evidenced by the capability in eliminating bowtie effects around CDP 600 up to CDP 800, eliminating diffraction effects around CDP 3900 to CDP 4050, and showing a seismic cross-section with better lateral resolution compared to the migration value of the aperture of 75 m and 200 m. Based on the seismic cross-section of migration results, the geological structure that can be identified is a fault that found in some CDP.